(untitled) (Ameghiniana, 2013)
This paper deals with a study carried at optical and electronic levels of mummífíed material of a new Ginkgoalean species, Baiera africana, found in middle-upper Triassic deposits from the Molteno Beds, Upper Umkomaas, Nata, Africa.